Algorithmic Rule Of Law In Local Government: Administrative Law Challenges In Automated Public Decision-Making In Indonesia - Muhammad Suhardi; Abdul Wahab (Universitas Sultan Ageng Tirtayasa, 2026)
This study examines the administrative law challenges arising from the use of automated public decision-making in local government in Indonesia and proposes an algorithmic rule of law framework as a normative basis for its regulation. The study employs normative legal research using statutory, conceptual, and comparative approaches. The legal materials analyzed include Indonesian laws and regulations concerning governmental administration, electronic-based government systems, personal data protection, and artificial intelligence policy, as well as selected European Union instruments as comparative references. The findings show that Indonesian law has provided a general foundation for digital government, but it has not yet specifically regulated the status, limits, and accountability of algorithmic systems in administrative decisions that affect citizens’ rights and interests. The main legal problems include the unclear boundary of algorithmic legality in public decision-making, the absence of a specific due process framework for automated decisions, the lack of integration between personal data protection and algorithmic accountability, and the risks posed by black-boxing and unequal digital capacity across local governments. In response, this study offers a reconstruction of the algorithmic rule of law framework, which includes a clear legal basis of authority, risk classification, meaningful human oversight, intelligible reasoning, audit trails, administrative remedies, and external supervision. These findings underline that local government digital transformation must remain firmly grounded in the rule of law, accountability, and administrative justice